PERANAN SEKTOR PERIKANAN DALAM PEMBANGUNAN WILAYAH DAN STRATEGI PENGEMBANGANYA DALAM RANGKA OTONOMI DAERAH KABUPATEN BALANGAN - Syahrida Ariani; Idiannor Mahyudin; Emmy Sri Mahreda (Fish Scientiae, 2019)
Balangan Regency has a fairly large waters resources and potentially increase revenues original areas, expected role of Government that has the authority Balangan Regency as Executive exploration and wealth management waters should be able to diginto the potential of the fishery to be more optimal in order to exercise the autonomy ofthe region. In General, this research aims to apply the techniques of planning regional development Balangan Regency. Whereas in particular this research aims to know the roleof the fisheries sector to the economy and setting the Balangan Regency alternative strategies for the development of fisheries sector in the framework of regional autonomy in Balangan Regency. Research methods used are descriptive qualitative, and used case studies approaches and analysis of the data used descriptive analysis, analysis of profit and SWOT analysis (Strategic Issues and problem identification). Based on the results of the SWOT analysis and the calculation of weighting matrix with QSP obtained the alternative order of precedence for the development strategy of the fishery as follows: 1) local government commitment to the development of the fisheriessector through the allocation of the budget, 2) of local government through the Office of PTPHPP improves the role of BBI and UPR to produce quality seeds and stem and have a certification, 3) increases the role and function of fisheries extension, officers, 4) increase the utilization potential of land fish breeding with commodities consider superior highvalued economically, 5) local government through the Department of agriculture TPHPP do coaching and mentoring to the public so as to enhance the community's knowledge andskills in mastering technology, 6) to facilitate the community to access capital to banking,7) need for regulatory policy and real step to cope with the high price of feed aquaculturethrough the improvement of irrigation channels and BBI, 8) local governments throughthe Exchange Service for industry, trade and cooperatives facilitates map marketing linefor fish farmers so that the price of fish could remain stable, 9) need to do coaching andmentoring to the community especially to the processed products to be verified products,10) Improved infrastructure facilities and function facilities and infrastructure production,110 of local Government more for socialize skim credit for the people KUR through thesocialization to the community.